Exploring Thermal Alliesthesia and Psychogeography Through Minimal Virtual Exposure - Ghifari, Abi Dzar; Isti Hidayati (Universitas Muhammadiyah Surakarta, 2026)
Individual perceptions of urban space are shaped by physical adaptations associated with their region of origin. These psychogeographic factors influence how the body adjusts to environmental changes, including the mechanism of homeostasis (the body’s ability to maintain internal balance), which results in different standards of thermal comfort among individuals. In the thermal context, homeostasis serves as a strong trigger for thermal alliesthesia, a condition in which sensations of comfort or discomfort arise in response to temperature changes relative to the body’s prior state. This study adopts an exploratory approach aimed at assessing the potential detection of such processes in a virtual setting with minimal exposure, using video-based observations of urban environments. Structural Equation Modeling (SEM) was employed to examine multivariate relationships between mood states, regional background, and perceptions of physical elements (brightness, shading), as well as their impact on route comfort. The findings indicate that homeostatic processes can still be detected in virtual settings and are positively influenced by psychogeographic background, thereby opening opportunities for applications in spatial design, further research, and place branding, even without direct on-site involvement.